The impact of AI-generated content on content consumption habits of Chinese social media users through Xiaohongshu application - Zhe, Chen; Srijinda, Prakaikavin (Edelweiss Applied Science and Technology, 2024)
This study aims to analyze the effects of artificial intelligence-generated content and human-generated content on user cognition, interaction and satisfaction in Xiaohongshu application. The samples are 500 active Xiaohongshu users in China’s first - and second-tier cities, including white-collar workers, students, freelancers selected through multi-stage random sampling. The research instrument is a questionnaire. Data were analyzed by statistical methods such as multiple linear regression analysis, T-test and Pearson correlation analysis were used to compare the differences between AI-generated content and human-generated content in terms of user satisfaction, time of use, recommendation quality, personalization satisfaction, content creativity and understanding of user needs. The findings revealed that AI-generated content shows significant advantages in improving user satisfaction and interaction, and the conclusions provide empirical support for the content optimization of social media platforms.